Urban-rural disparities in skilled birth attendance among women in Ethiopia: Multivariate decomposition analysis. - Tsegereda Abebe Andargie; Emebet Birhanu Lealem; Betelhem Abebe Andargie (PLoS ONE)
Introduction Skilled birth attendants play an important role in reducing maternal mortality. Although Ethiopia has shown a remarkable reduction in maternal mortality, maternal health service utilization, such as skilled birth attendance, remains low. Thus, this study aims to assess the urban-rural disparity in skilled birth attendance in Ethiopia using the 2019 Ethiopian mini demographic health survey. Methods and materials The study was based on data obtained from demographic and health surveys in Ethiopia. A total weighted sample of 5,527 women who gave birth within 5 years preceding the survey was included. The result of descriptive statistics was reported using the frequency, percentages, graphs, and tables. A multivariate decomposition analysis was used to identify factors contributing to the disparity of skilled birth attendance across residence. Statistical significance was defined at a 95% confidence interval with a p-value of less than 0.05. Result Skilled birth attendance utilization among women in Ethiopia was 49.8% (95% CI: 48.5-51.1). The disparity in skilled birth attendance coverage between urban and rural areas was significantly high (Urban coverage was 72.1% and rural coverage was 42.5%). Endowment coefficients (women's characteristics) explained 88% of the urban-rural disparity in the magnitude of skilled birth attendance. Women with secondary and above educational status, four or more antenatal care visits, households with televisions and radio, women in the richest wealth index and women with five or more parity were the determinants that explained the urban-rural disparity in skilled birth attendance. Conclusion and recommendations There was a significant disparity in skilled birth attendance utilization between urban and rural areas. Factors like maternal education, wealth status, antenatal care visits, and media access explained the disparity. To attain equitable progress towards universal coverage of SBA, special efforts and resources should be targeted towards rural women. Initiatives aimed at enhancing access to health services and health care consultations for the rural community are also recommended.